The state of the biogeometric profile of the posture of young athletes specializing in hand-to-hand combat as a prerequisite for the development of corrective and preventive measures - Vitalii Kashuba; Аndrii Radchenko; Yuri Radchenko; Ilia Vako; Vitaly Usychenko (Фізична реабілітація та рекреаційно-оздоровчі технології)
Purpose: The purpose of the presented scientific research was, on the basis of somatoscopic indicators, to substantiate the biological prerequisites for the introduction of corrective and preventive measures into the educational and training process of young athletes specializing in hand-to-hand combat.